PENURUNAN TINGKAT KECEMASAN MAHASISWA DENGAN PEMBERIAN TERAPI MUSIK DI SEKOLAH TINGGI ILMU KESEHATAN dr. SOEBANDI JEMBER - Tirta Vira Cakti Yudha (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
The cause of anxiety is because of the thesis burden and the inability to manage the finishing time and short semester. World anxiety prevalence reaches 20%, anxiety in Indonesia ranges from 2-5% (Pietra, 2001). Anxiety number at STIKES dr. Soebandi Jember as many as 17 students in the eighth semester.The purpose of this study was to determine the effectiveness of reducing the level of student anxiety by providing music therapy at STIKES dr. Soebandi Jember. This type of research is quasy experiment with one group pre-test and post-test treatment design. The research sample of 17 STIKES students, dr. Soebandi Jember Undergraduate nursing program in the eighth semester uses a total sampling technique with inclusion criteria willing to be a respondent and can measure anxiety levels. Analysis using Wilcoxon match pairs test with p <0.05. The results of the study prior to music therapy were moderate anxiety by 11 students (68.75%), and mild anxiety by 5 students (31.25%). Anxiety level after music therapy is a mild anxiety level of 8 students (50%), moderate anxiety of 5 students (31.25%) and there are students who do not experience anxiety as much as 3 students (18.75%), the average decrease in anxiety 3.06. Wilcoxon test results obtained p value = 0.007, which means there are differences in anxiety levels in students who prepare the final project before and after being given music therapy. Koping cope with anxiety by listening to music. Psychologically music relaxes with sedative music. For this reason, effective music is used as a therapy to reduce anxiety